Myxobolus bragantinus n. sp. (Cnidaria: Myxosporea) from the gill filaments of the redeye mullet, Mugil rubrioculus (Mugiliformes: Mugilidae), on the eastern Amazon coast - Cardim, Joyce; Silva, Diehgo; Hamoy, Igor; Matos, Edilson; Abrunhosa, Fernando (Zootaxa, 2018)
Mullets (Mugilidae) are economically-important fish exploited extensively by artisanal fisheries on the Amazon coast of Brazil. In the present study, 150 specimens of redeye mullet (Mugil rubrioculus) acquired from the public fish market were examined, and the gill filaments of 90 (60%) were found to be infected with spores of Myxobolus. The mature spores were spherical, with a mean diameter of 6.28±0.33 μm, and had polar capsules of equal size (2.47±0.34 μm in length and 1.58±0.27 μm in width). The 18S rRNA sequence of the parasite was compared with those of other myxosporidian species available in the GenBank database. The morphological and molecular characteristics of the parasite indicate strongly the existence of a new species, denominated Myxobolus bragantinus n. sp., the first case of a new myxosporidian species to be found in this host. [Zoobank: urn:lsid:zoobank.org:act:E00F72E1-9302-423F-BA4E-51C05D0770C8]